Secrets of the temple : how the Federal Reserve runs the country - Greider, William (New York : Simon & Schuster, 1989)
Reveals how the Federal Reserve under Paul Volcker engineered changes in America's economy.
"A Touchstone book."
Includes bibliographical references (p. [733]-766) and index.
oif 30/10/15
Loans
Keywords: Federal Reserve banks; Monetary policy; Banks and banking; Finance